A study of lipid oil production from Chlorophyta species as biodiesel potential / Zuraidah Rasep ... [et al.] - Rasep, Zuraidah; Muhammmad Amin, Fatein Azrin Megat; Mamat, Suhaini; Yahya, Norilhamiah; Law, Jeng Yih; Mohd Ghazali, Mohd Syazwan; Isa, Nadia (2014)
The rapid increase of carbon dioxide (CO2) concentration in the atmosphere and high demand for energy security had led to an increased commercial interest in renewable fuels. Green algae from chlorophyta species are favorable feedstock due to their high oil content and fast growth rate. This study investigated the extraction of lipid oil from chlorophyta species collected from Teluk Pelanduk, Port Dickson by using a soxhlet extraction method. Solvent lipid oil extraction from chlorophyta species focus on the efficiency of three different solvents (hexane, ethanol and acetone) and the composition of fatty acids in the lipid oil. Hexane proved to be the most efficient solvent for chlorophyta species extraction with percentage lipid oil of 4.08%, followed by acetone (3.98%) and ethanol (1.47%).The lipid oil extract from chlorophyta species was analyzed using gas chromatography to identify the fatty acid components in the lipid oil extracts. The results showed that green algae from chlorophyta species have required fatty acid profile for conversion to high quality of biodiesel. From the results obtained, it is interesting to highlight that green algae from chlorophyta species have the required fatty acid profile for conversion to high quality of biodiesel.